2022
DOI: 10.1111/gcb.16407
|View full text |Cite
|
Sign up to set email alerts
|

isocalcR: An R package to streamline and standardize stable isotope calculations in ecological research

Abstract: Plants transfer, on average, 0.33 Pg carbon from the atmosphere to the biosphere each day, removing nearly one-third of anthropogenic CO 2 emissions annually (Friedlingstein et al., 2020). This enormous transfer of CO 2 is accompanied by similarly large, unavoidable losses of H 2 O vapor (Schlesinger & Jasechko, 2014), which plants have evolved to minimize through a combination of morphological (e.g. waxy cuticle, sunken stomates) (Wang et al., 2022) and physiological strategies (e.g. stomatal aperture control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Gong et al (2022) analyzed tree ring 13 C series across the globe using the iWUE mes model, and reported that iWUE sim model significantly overestimated iWUE (by c. 100%) and the rate of iWUE gain with time or C a (by c. 70%) during the 20th century. This finding has been confirmed by studies carried out in distinct ecosystems (Bing et al, 2022;Mathias and Hudiburg, 2022). Failure to consider g m must lead to an overestimated historical trend as implied by the partial derivative of iWUE mes (Equation 11) (Gong et al, 2022):…”
Section: Uncertainty In Iwue Sim Estimation Associated With Mesophyll...mentioning
confidence: 73%
See 1 more Smart Citation
“…Gong et al (2022) analyzed tree ring 13 C series across the globe using the iWUE mes model, and reported that iWUE sim model significantly overestimated iWUE (by c. 100%) and the rate of iWUE gain with time or C a (by c. 70%) during the 20th century. This finding has been confirmed by studies carried out in distinct ecosystems (Bing et al, 2022;Mathias and Hudiburg, 2022). Failure to consider g m must lead to an overestimated historical trend as implied by the partial derivative of iWUE mes (Equation 11) (Gong et al, 2022):…”
Section: Uncertainty In Iwue Sim Estimation Associated With Mesophyll...mentioning
confidence: 73%
“…The classical iWUE sim model has been shown to strongly overestimate iWUE and its historical trends due to the neglect of g m associated effect, limiting its use in quantitative studies. iWUE mes is suggested as a useful, simplified model for quantitative estimation of iWUE, which has been included in a standardized, open-source tool (R package) for calculation of iWUE from stable isotope signatures ( Mathias and Hudiburg, 2022 ). Nonetheless, the formulation of iWUE mes could still be further improved.…”
Section: Conclusion Remarksmentioning
confidence: 99%
“…Last, we calculated iWUE according to Farquhar et al (1989) usingiWUEgoodbreak=Anetgnormalsgoodbreak=normalCnormalanormalCnormali1.6,$$ \mathrm{iWUE}=\frac{A_{\mathrm{net}}}{g_{\mathrm{s}}}=\frac{\left({\mathrm{C}}_{\mathrm{a}}‐{\mathrm{C}}_{\mathrm{i}}\right)}{1.6}, $$where 1.6 is the constant ratio for the diffusivity of CO 2 and H 2 O vapor in the air. All carbon isotope calculations described were performed using the R package “isocalcR” (Mathias & Hudiburg, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Last, we calculated iWUE according to Farquhar et al (1989) using where 1.6 is the constant ratio for the diffusivity of CO 2 and H 2 O vapor in the air. All carbon isotope calculations described were performed using the R package "isocalcR" (Mathias & Hudiburg, 2022).…”
Section: Carbon Isotope Analysis Of Tree Ringsmentioning
confidence: 99%
“…While rapid WUE quantification method is yet to be applied in bioenergy research, it has been successfully used in conjunction with quantitative trait loci analysis to identify genes that promote enhanced WUE in cereals (Chen et al, 2011). The application of these emerging methods along with standardized approaches that facilitate the process of estimating WUE (Mathias & Hudiburg, 2022) could substantially expedite the identification of transgenic bioenergy crops for high WUE traits.…”
Section: Use Of Stable Isotopes To Investigate Water and Nutrient Use...mentioning
confidence: 99%